Permafrost presence and distribution in the Chic-Chocs Mountains, Gaspésie, Québec - Gray, James; Brown, Roger (Géographie physique et Quaternaire)

(untitled) (Les Presses de l’Université de Montréal, 1979)
Ground temperature studies, begun in 1977, revealed the presence of permafrost at the summit of Mont Jacques-Cartier (1270 m), in Gaspésie. Temperature profile data to a depth of 30 m in a drill hole indicates an active layer slightly thicker than 5.75 m, overlying a permafrost body extending beyond the base of the hole. Downward extrapolation of the profile, based on heat flow data and thermal conductivity measurements show that this permafrost body is from 45-60 m thick. That the permafrost is contemporary is indicated by the proximity of the permafrost table to the surface, by the low mean annual air temperature for the site (-3°C to -5°C), and by the lack of a thick insulative blanket of snow in the winter. A mean annual ground surface temperature of -1°C to -1.5°C is estimated for the site. The Mont Jacques-Cartier data enabled a regional lower limit of 1,000 — 1,100 m to be established for extensive permafrost in the Chic-Chocs Mountains in treeless exposed situations. A limited amount of ground temperature data from Mont Logan and Mont Albert tends to confirm the validity of this regional limit, which was then used, in association with our knowledge of the vegetation cover, to map the distribution of extensive permafrost bodies for the entire eastern Chic-Chocs Mountains. Although not observed in this study, permafrost may exist below this regional limit, in either coarse debris accumulations, or in organic terrains at high altitudes subject to sufficiently thick accumulations of peat